Co-Existence of Sarcoidosis and Sjögren’s Syndrome with Hypercalcemia and Renal Involvement: A Case Report and Literature Review - Xu, Jing; Yang, Yumei; Chen, Dandan; Lu, Zhiqiang; Ge, Junbo; Li, Xiaomu; Gao, Xin (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Background: Sarcoidosis and Sjögren's syndrome (SS) are chronic multi-system inflammatory diseases of unknown origin that most commonly attack the salivary glands. Both of the diseases have vague and non-specific symptoms, causing difficulties for the clinicians to distinguish between the two diseases. Main diagnostic criteria of SS exclude sarcoidosis. However, a co-existence of both diseases should be noted. Here, a case of co-existing sarcoidosis and Sjögren's syndrome is reported, complicated with severe hypercalcemia and renal failure, in addition to a literature review. Case Presentation: A 71-year-old man visited our hospital complaining of daily progressive oral dryness, thirst, and blurred vision with a feeling of dry eyes for a one-year duration. His physical examination showed enlargement of both sides of cervical and supraclavicular lymph nodes. Lung auscultation showed decreased breath sounds with bibasilar inspiratory crackles. However, initial laboratory results revealed severe hypercalcemia with moderate hypercalciuria and renal failure. The final diagnosis was co-existing SS and sarcoidosis according to clinical, radiological, and laboratory data. The patient received oral prednisone therapy for 18 months. After a follow-up of years, the serum calcium concentration, renal function, and chest CT scan remained normal after prednisone treatment stopped for more than 18 months. Conclusion: In the literature, calcium metabolic disorder and renal involvement have not been reported among patients with Sarcoidosis and Sjögren's syndrome, suggesting that calcium metabolic disorder may be underestimated. Serum and urine calcium concentration should be measured in addition to routine laboratory tests.
Keywords: sarcoidosis